An overview of plant species and substrate materials or green roof system in tropical climate urban environment - Chow M.F.; Bakar M.F.A.; Wong J.K. (American Institute of Physics Inc., 2023)
Green roofs have become a popular strategy in urban stormwater management in the recent years. However, the plant species and substrate composition of green roofs can vary substantially due to design characteristics and environmental conditions. This study is aimed to review all the plant species and substrate composition that applied in both temperate and tropical climate countries. Current studies on green roofs involving different plant species, substrate types and environmental conditions are reviewed and evaluated in detail. Better understandings on the plant species and substrate composition for green roofs will be benefiting to the successful implementation of green roof system in the tropical climate urban environment. 2018 Author(s).